An Experimental Study on the Adsorption and Desorption of Cu(II) in Silty Clay - Shuang Xie; Zhang Wen; Hongbin Zhan; Menggui Jin (Geofluids)
Heavy metals such as Cu(II) are widespread in the environment, and the impact of heavy metals on the environment of soils depends on the ability of soils to immobilize these pollutants. It is necessary to investigate the mechanism of interaction between heavy metal and soil from a soil remediation perspective. In this study, a series of experiments were conducted to investigate the adsorption and desorption behavior of Cu(II) in silty clay. Several impact factors such as pH, organic matter, temperature, and coexisted ions Zn(II) were considered. It was found that the adsorption process reached equilibrium after 4 hours of the experiment, and the data can be fitted well by the Elovich model and the double-constant model for the kinetic sorption process. The isothermal adsorption results showed that the adsorption rate reached a peak value when the initial concentration was about 20 mg L−1. The decrease of H+ can increase the adsorption activity of Cu(II) and reduce the ability of the desorption of Cu(II) ions. The adsorption capacity of Cu(II) is less than the desorption capacity under the condition of strong acidity and low concentration of Cu(II). In addition, the adsorption capacity of the native soil on Cu(II) was larger than that of the soil with the removal of organic matter, while the opposite was true for the desorption capacity on Cu(II). The maximum adsorption of Cu(II) occurred at 35°C for this study, and the binding energy increased as the temperature increased. Thermodynamic analysis revealed that the adsorption process of Cu(II) was spontaneous and endothermic. The Freundlich, Langmuir, Temkin, and Henry adsorption models were used for analyzing the adsorption isotherm of Cu(II), and it was found that the Freundlich model agreed the best with the experimental data compared with other three models. The results of the competitive adsorption experiments indicated that the competitive capacity of Cu(II) was greater than that of Zn(II) in low-permeability media such as silty clay, and the existence of binary metals can weaken the adsorption force between the single metal and the soil surface.